Diversity of macrobenthos in the mangrove forest of Kuala Sibuti, Miri, Sarawak - Mustafa Kamal, Abu Hena; Idris, Mohd Hanafi; Mohd Yusop, Khairul Rasyid; Bhuiyan, Md. Khurshid Alam; Hoque, Mohammad Nesarul; Kumar, Uttam (Department of Biology, Faculty of Science, Universiti Putra Malaysia, 2016)
The diversity of mangrove macrobenthos assemblages at mangrove forest of Kuala Sibuti, Miri, Sarawak was investigated for northeast monsoon and inter monsoon season. The aim of this study was to determine the diversity and composition of macrobenthos in the Kuala Sibuti mangrove forest. Sampling was carried out at 3 different locations during each monsoon. In macrobenthos assemblages, bivalves (49%) was the most diverse and abundant followed by gastropods (23%), polychaetes (17%) and crustaceans (10%). A total of 25 species of macrobenthos have been recorded during the study period. Studies found that sediment texture plays an important role in the ecology of benthic invertebrates. Polychaete was found be influenced by the percentage of soil texture, while temperature and pH have had little influence on the macrobenthos assemblages in this mangrove forest ecosystem.